Brain of the African wild dog. I. Anatomy, architecture, and volumetrics. Issue 18 (2nd September 2020) - Chengetanai, Samson; Tenley, Jonathan D.; Bertelsen, Mads F.; Hård, Therese; Bhagwandin, Adhil; Haagensen, Mark; Tang, Cheuk Y.; Wang, Victoria X.; Wicinski, Bridget; Hof, Patrick R.; Manger, Paul R.; Spocter, Muhammad A.
Abstract: The African wild dog is endemic to sub‐Saharan Africa and belongs to the family Canidae which includes domestic dogs and their closest relatives (i.e., wolves, coyotes, jackals, dingoes, and foxes). The African wild dog is known for its highly social behavior, co‐ordinated pack predation, and striking vocal repertoire, but little is known about its brain and whether it differs in any significant way from that of other canids. We employed gross anatomical observation, magnetic resonance imaging, and classical neuroanatomical staining to provide a broad overview of the structure of the African wild dog brain. Our results reveal a mean brain mass of 154.08 g, with an encephalization quotient of 1.73, indicating that the African wild dog has a relatively large brain size. Analysis of the various structures that comprise their brains and their topological inter‐relationships, as well as the areas and volumes of the corpus callosum, ventricular system, hippocampus, amygdala, cerebellum and the gyrification index, all reveal that the African wild dog brain is, in general, similar to that of other mammals, and very similar to that of other carnivorans. While at this level of analysis we do not find any striking specializations within the brain of the African wild dog, apart from a relatively large brain size, the observations made indicate that more detailed analyses of specific neural systems, particularly those involved in sensorimotor processing, sociality or cognition, may reveal features that are either unique to this species or shared among the Canidae to the exclusion of other Carnivora. Abstract : Photograph of the lateral surface of the African wild dog brain. The African wild dog has a relatively large brain, but this appears to be related to a reduction in body mass during its evolutionary history, rather than an increase in brain mass in response to a complex social environment. In this image dorsal is to the top and rostral toward the left. Scale bar = 1 cm.